1990
DOI: 10.1159/000186133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drug Additives to Peritoneal Dialysis Solutions on the Viability and Function of Mouse Peritoneal Cells

Abstract: Peritoneal dialysis (PD) solutions and therapeutic drugs frequently added to PD solutions in clinical practice have been shown to reduce the viability and to impair the function of mouse peritoneal cells. The cytotoxicity of PD solutions, directly related to the dextrose concentration, was more marked towards resident than elicited peritoneal cells. None of the drug additives, heparin and insulin amongst them, were cytotoxic when tested alone or combined with 4.25% PD solution, with the exception of phosphatid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Conversely, the reduced viability of mesothelium treated with acidic fluids was mainly attributed by other investigators to the low pH of the solution [14]. It is interesting to note that other in vitro studies, exposing peritoneal macrophages [2] or mesothelial cells [3] to high-glucose, lactated, and acidic solutions for PD, suggested a relevant cytotoxic effect of the glucose concentration per se.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Conversely, the reduced viability of mesothelium treated with acidic fluids was mainly attributed by other investigators to the low pH of the solution [14]. It is interesting to note that other in vitro studies, exposing peritoneal macrophages [2] or mesothelial cells [3] to high-glucose, lactated, and acidic solutions for PD, suggested a relevant cytotoxic effect of the glucose concentration per se.…”
Section: Discussionmentioning
confidence: 96%
“…Several lines of investigation revealed detrimental effects induced by glucose-enriched, lactate-buffered peritoneal dialysis (PD) solutions, commonly used in clinical wards upon acutely exposed mesothelial cells in culture [1, 2, 3, 4]. The detected changes included: reduced cell viability [2, 3, 4], a substantial decrease of interleukin 6 and prostaglandin F 1α synthesis [5], inhibition of cell proliferation [6], a drop in the intracellular concentration of reduced glutathione [7], and even increased generation of hydrogen peroxide [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We pro pose that even a low-concentration chronic intraperitoneal administration of phosphatidylcholine may disturb the functional integrity of the mésothélium. Furthermore, Gag-non et al [4] showed that phosphatidylcholine cytotoxicity on peritoneal macrophages increases when the cells are incubated in hypertonic fluid rather than in the buffered medium. Based on this observation, one may speculate that in vivo repair of injured cells is more efficient than in vitro when the cells are cultured in medium, the composition of which only partially resembles the composition of body fluid: we propose that our observations on the toxicity of various factors (osmotic solutes, antiseptics, phosphatidylchonile) to mesothelial cells in vitro reflect the real situation in vivo although the intensity of this process in the body milieu may be lower.…”
Section: Discussionmentioning
confidence: 99%
“…Peritoneal macrophages and neutrophils are potential sources of free radicals. However, the high osmolality and low pH of the dialysis solution is toxic to these cells, reducing their viability (51,52,53) and decreasing their capacity to generate oxygen-derived free radicals (54)(55)(56). During peritoneal dialysis, the pH of the dialysate solution is adjusted to normal within 30 60 min (57), while its osmolality is continuously decreasing due to absorption of osmotic solutes and flow of water into the peritoneal cavity.…”
mentioning
confidence: 99%